2015
DOI: 10.18632/oncotarget.5154
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α9 gene promoter is hypermethylated and downregulated in nasopharyngeal carcinoma

Abstract: Epigenetic silencing of tumor suppressor genes (TSGs) by promoter methylation can be an early event in the multi-step process of carcinogenesis. Human chromosome 3 contains clusters of TSGs involved in many cancer types including nasopharyngeal carcinoma (NPC), the most common cancer in Southern China. Among ten candidate TSGs identified in chromosome 3 using NotI microarray, ITGA9 and WNT7A could be validated. 5′-aza-2′ deoxycytidine treatment restored the expression of ITGA9 and WNT7A in two NPC cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…DNA methylation, which is a common mechanism in epigenetic alterations, may be correlated with NPC ( Jiang et al, 2015 , Nawaz et al, 2015a ). Promoter methylation of tumor suppressor genes (TSGs), such as calcium channel voltage-dependent alpha 2/delta subunit 3 ( CACNA2D3 ) and cadherin 4 ( CDH4 ), may play a crucial role in NPC development and progression ( Wong et al, 2013 , Du et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation, which is a common mechanism in epigenetic alterations, may be correlated with NPC ( Jiang et al, 2015 , Nawaz et al, 2015a ). Promoter methylation of tumor suppressor genes (TSGs), such as calcium channel voltage-dependent alpha 2/delta subunit 3 ( CACNA2D3 ) and cadherin 4 ( CDH4 ), may play a crucial role in NPC development and progression ( Wong et al, 2013 , Du et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that upregulation of ITGA9 in response to a decrease in miR-125b levels in metastatic melanoma is responsible for melanoma tumor cell migration and invasion (63). In addition, ITGA9 is associated with other types of cancer, including nasopharyngeal carcinoma (64), breast cancer (65) and colorectal cancer (66). PIK3R1 is a target of miR-29b and miR-221, which may enhance chemosensitivity to gemcitabine in HuH28 human CCA cells (67).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ITGA9 mRNA level was significantly downregulated in bladder cancer tissues compared with the corresponding adjacent to the tumor tissues [ 33 ]. Nawaz et al have reported that ITGA9 promoter was downregulated by aberrant hypermethylation in promoter and probably facilitated the process of nasopharyngeal carcinoma [ 34 ]. Nevertheless, our data revealed that ITGA9 not only restrains tumor growth but also suppresses tumor metastasis to prevent HCC progression.…”
Section: Discussionmentioning
confidence: 99%